Έλεγχος επίδρασης σκευάσματος αιθέριων ελαίων ευκαλύπτου και δεντρολίβανου στον τετράνυχο (Tetranychus Urticae) - Πολυβίου, Πολύβιος (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Two spotted spider mite, with the scientific name Tetranychus urticae, is one of the most important plant pests because it can be found in greenhouses and open air cultures. In this study the effect of a biological pesticide which contains essential oils from Eucalyptus sp. and Rosmarinus officinalis was investigated. Initially the mortality curves were generated and afterwards the LC50/LC95 values were calculated for 24 hours after spraying which were 1.08% (0.96 - 1.21) and 4.40% (3.34 - 5.51%), respectively and for 48 hours after spraying which were 0.97% (0.86 - 1.08) and 3.43% (2.72 - 4.14), respectively. Then, the biopesticide was tested for its effect on fecundity with the concentrations of LC0 (water) for the control, LC10 corresponding to 0.3% of the formulation and LC30 corresponding to 0.62% of the formulation dissolved in water. The mean number (±1 standard deviation) of the eggs was 27.95 (± 19.99) for the control, 17.8 (± 12.12) for the LC10 concentration and 16.4 (± 11.96) for the LC30 concentration. Also it was studied for its effect on the hatching of the eggs with the same concentrations. For the concentrations of LC0, LC10, and LC30 the eggs that hatched was 93.75, 87.5 and 68.8% of the eggs placed. These essential oils can be used to combat the acari pest from the crops.
Keywords: Eucalyptus; Eucalyptus sp; Rosemary; Rosmarinus officinalis; Two spotted spider mite; Tetranychus urticae; Fecundity; Essential oils; Ευκάλυπτος; Δενδρολίβανο; Τετράνυχος; Αιθέρια έλαια; Ωοτοκία